Pieczęcie instytucji sądowych miast Wielkopolski do końca XVIII w. a heraldyka miejska - Adamczewski, Marek (Acta Universitatis Lodziensis. Folia Historica, 1999)
Authors of ideas and creators of judical seals in Old Poland (to 1791) were completely free in creating of seal pictures. However we can observe a connection between judical and municipal iconography of seals. Rules for creating of seal pictures were established by decisions of the Great Sejm in June and October 1791. Using of judical seals for studies on town heraldry may give us unexpected results. For example we are able to revise previous settlements concerning origins of some town arms as well as heraldic symbols. We would be able to use judical seals more effectively for scientific studies, when we had at our disposal complete histories of cities and towns, lists of municipal officials as well as a knowledge of municipal judicature in old small towns.